Desertification Studies in the Sudan - Gamri, Tairg EI; Nasikh, E EI (Annals of Arid Zone, 2016)
Sudan is a vast country with an area of about 2.5 million square km (2/3rd of the area is arid or semi-arid) and hosts an estimated population of about 31 million people. It is concluded from the findings of various studies that 12,000 years ago natural deserts constituted only small fraction of the Sudanese territories. However. recently, especially during the second half of the previous century the arid and semi-arid regions of the country were subjected to different forms of land degradation. The area affected by drought and desertification is amounting to about 50.5% of the total area of the country. Defore~tation is considered by some authors as the main cause of land degradation in the country. This paper presents an overview of the different desertification studies executed in the country. Howeve.r. special emphasis is put in the studies in the subjects of soil and water resources. Arid land agriculture and biodiversity are also discussed in some detail. The indicators of soil and land degradation are identified and the causative factors are also highlighted. The characteristics of rainfall and the striking advancement of the use of the empirical-statistical rainfall prediction models are also illustrated. Research in water conservation techniques like water harvesting, supplementary irrigation and canal lining is also reviewed. Studies on the impacts of irrigated desert agriculture with special emphasis to Urn Jawaseer Project are also discussed. The Project proved to upgrade the livelihood of the beneficiaries and to protect the environment.